Observations on the reproduction and ecology of the tropical montane toad, Bufo holdridgei Taylor in Costa Rica - Novak, Richard M. (1975)
Reproductive behavior of the mute. tympanumless montane Costa Rican toad. Bufo holdridgei is described and discussed. The species has one of the smallest egg complements and one of the largest egg sizes reported for the genus. Eggs and larvae are described and limited ecological observations reported. Size, pigmentation and number of eggs suggest less relationship with the monotypic genus Crepidophryne than has been postulated by some authors.